Development, characterisation and biocompatibility analysis of a collagen-gelatin-hydroxyapatite scaffold for guided bone regeneration = Desarrollo, caracterización y análisis de biocompatibilidad de un andamio de colágeno-hidroxiapatita para la regeneración ósea guiada - Shankar, Preethi
Guided Bone Regeneration (GBR) is the choice of treatment for improving the horizontal and vertical bone volume through bone grafting. GBR membranes work on the principle of preventing epithelial migration into the defect space while maintaining the space for cell migration and differentiation at the defect site. Hydroxyapatite has been commonly used as a bone graft for infrabony defects. The study was conducted at the Department of Biomaterials at Saveetha Dental College. GBR membrane was prepared and its material characterization was done using Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX) analysis, Fourier Transform Infrared Radiation (FTIR), and Confocal Analysis. The developed GBR membrane revealed SEM properties conducive to cell attachment. EDX and FTIR analysis showed the successful development of the collagen-gelatin-hydroxyapatite membrane. Cell culture and confocal analysis revealed excellent biocompatibility with a homogenous layer of viable cells. The developed composite GBR membrane is a biogenic membrane with relevant biomineralization potential that should be applied for GBR applications.